Mathematics Education in Restructuring the Current Impediment Affecting Economic Growth: Issues and Way Forward - Bulus, Shiaki O.; Yukwa, Bernard Alpha (Darul Yasin Al Sys, 2025)
Nigeria as developing nation needs mathematics at all walks of life that can consider restructuring of its economy very requisite and create innovative programmes through technology to improve the economic growth of the country. In this case, this paper examined the role of mathematics education in restructuring the current challenges affecting Nigeria economic growth. It presented six issues affecting the economy and through mathematics, the researchers pointed out all ways those highlighted issues can be resolved. From the way-forward enumerated, it was discovered that all government agency should organized empowerment programmes to young Nigerians with zeal of uplifting them from poverty and dependent. Through guiding it learner with basic scientific and technological skills that mathematics plays a center role in that Area.